Prinsip Kebersamaan Dalam Hukum Investasi Undang-Undang Nomor 11 Tahun 2020 Tentang Cipta Kerja: Politik Hukum Kepentingan Investasi Ataukah Kesejahteraan Masyarakat - Dewi Sukma Kristianti (PAMALI: Pattimura Magister Law Review, 2021)
Introductioan: Investment is a necessity that cannot be denied in development activities, especially economic development. This can be seen in studies or in the field of development economics, investment is one of the important factors to obtain capital for the economic development of a country. The goal of development in Indonesia is to realize social justice for all Indonesian people. So that the principle of togetherness is the basis and effort to realize the ideals of welfare and social justice for all Indonesian people.Purposes of the Research: The purpose of writing this article is to identify and analyze the principle of togetherness as a legal politics of the Job Creation Act in an interdisciplinary manner.Methods of the Research: The method used in this article uses a normative juridical research method with a multidisciplinary approach.Findings of the Research: One of the regulations in the investment sector is the Job Creation Law, the principle of togetherness in legal politics that underlies and focuses only on investment interests, so that the goal of realizing social justice is a very long goal. This can be seen from a number of articles in the Job Creation Law, both explicitly and implicitly, indicating several provisions that must be regulated in investment law according to various investment theories.